The Role of Intrapartum Ultrasound to Predict Outcome of Delivery: Penggunaan Ultrasonografi Intrapartum untuk Memprediksi Luaran Persalinan - Yakob Togar Simatupang; Yongki Wenas; Januar Simatupang (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objective: To predict outcome of delivery by using ultrasound measurements consisting angle of progression, and head perineum distance.Methods: Sixtytwo parturients assigned in cohort prospective study. Ultrasound examination begin with identifying the cephalic position by placement of transducer on suprapubic region. The angle of progression is obtained trans-labially, head perineum distance and cervical dilation trans-perineally. Ultrasound findings of Nuchal cord, caput, moulding, occiput posterior position then compared with conventional findings. Labour is observed, outcomes are grouped into vaginal delivery and cesarean section.Results: Thirty-six women went for vaginal delivery, 26 underwent cesarean section. Independent T-test showed significant differences of the angle of progression (121.11o vs 88.85o) and head perineum distance (5.15 cm vs 7.26 cm) between the two groups. Linear regression test found a negative correlation on how the angle of progression affecting head perineum distance p-value <0.05 , R2 0.684, (r) – 0.827. Cervical dilation measurements both ultrasound and digital examination were assessed with the Bland-Altman reliability test with level of agreement (-1.0 cm) – (1.2 cm). Receiver Operating Characteristic curve showed cut-off value >101o angle of progression predicts vaginal delivery, area under curve 0.902 and positive likelihood ratio 4.4. Kappa reliability testing for nuchal cord, caput, moulding, and occiput posterior are 0.919, 0.938, 0.384, 0.681 respectively.Conclusion: Intrapartum ultrasound able to predict the outcome of delivery, digital examination of cervical dilation is the mainstay of measurement. Ultrasound able to rule out the presence of nuchal cord, caput, and occiput posterior. Keywords: angle of progression, head perineum distance, intrapartum ultrasound. Abstrak Tujuan: Mengetahui besar sudut penurunan kepala dan jarak kepala ke perineum dengan ultrasonografi intrapartum dalam memprediksi luaran persalinan. Metode: Enam puluh dua ibu bersalin dilakukan pemeriksaan ultrasonografi intrapartum. Identifikasi posisi kepala dengan meletakan transduser di suprapubik, sudut penurunan kepala secara translabial, jarak kepala ke perineum dan nilai dilatasi serviks secara transperineal. Lilitan tali pusat, kaput, molase, dan oksiput posterior pada temuan ulstrasonografi dibandingkan dengan hasil pemeriksaan konvensional. Observasi persalinan dilakukan, di kelompokan untuk persalinan pervaginam dan seksio sesarea.Hasil: Didapatkan 36 persalinan pervaginam dan 26 seksio sesarea. Uji – t secara signifikan berbeda, nilai sudut penurunan kepala (121,11o vs 88,85o), jarak kepala ke perineum (5,15 cm vs 7,26 cm) pada kedua kelompok. Uji regresi linier sudut penurunan kepala dan pengaruhnya terhadap jarak kepala ke perineum berkorelasi negatif p <0.05, R2 0.684, (r) – 0.827. Batas kesepakatan nilai dilatasi serviks kedua metode diuji dengan uji reliabilitas Bland-Altman dengan batas kesepakatan sebesar (-1.0) cm – (1.2) cm. Sudut penurunan kepala memprediksi persalinan pervaginam sebesar >101o, uji diagnostik dengan kurva Receiver Operating Characteristic didapatkan area dibawah kurva 0.902, rasio kemungkinan positif 4,4. Uji reliabilitas Kappa lilitan tali pusat, kaput ,molase, dan oksiput posterior berturut-turut (k) = 0.919, 0.938, 0.384, dan 0.681. Kesimpulan: Penggunaan ultrasonografi intrapartum dapat memprediksi luaran persalinan, pemriksaan dalam tetap menjadi pemeriksaan utama dalam menilai dilatasi serviks, ultrasnografi mampu mendeteksi lilitan tali pusat, kaput, dan posisi oksiput posterior.Kata kunci: Jarak kepala ke perineum, sudut penurunan kepala, Ultrasonografi intrapartum.